2022
DOI: 10.1021/acsami.1c24801
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ferroelectric In2Se3 in Polysulfide Shuttling and Charging/Discharging Kinetics in Lithium/Sodium–Sulfur Batteries

Abstract: Lithium–sulfur (Li–S) and sodium–sulfur (Na–S) batteries, with the advantages of ultrahigh energy density, natural abundance, and ecofriendliness, are regarded as next-generation rechargeable batteries. However, polysulfide shuttling and sluggish charging/discharging kinetics in sulfur cathodes severely hamper their practical applications. In this study, via employing first-principles calculations, we investigate two-dimensional ferroelectric In2Se3 as a promising additive to overcome these obstacles. Our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…, where E(Li 2 S@MXene), E(Li 2 S) and E(MXene) denote the electric energies of Li 2 S adsorbed MXene, the Li 2 S molecule and MXene, respectively. The free energy change during the discharging process is evaluated using our previous method: 32…”
Section: Computational Detailsmentioning
confidence: 99%
“…, where E(Li 2 S@MXene), E(Li 2 S) and E(MXene) denote the electric energies of Li 2 S adsorbed MXene, the Li 2 S molecule and MXene, respectively. The free energy change during the discharging process is evaluated using our previous method: 32…”
Section: Computational Detailsmentioning
confidence: 99%
“…With the continuous development of human society, new energy materials, especially electronic consumables and power electric vehicles, have made amazing achievements over the past decade. As an important part of the secondary battery family, Li-ion batteries (LIBs) have been successfully used in commercial applications. , Unfortunately, their commercial anode is mainly focused on stable graphite-like materials due to the issues of Li dendrites and short circuits in lithium metal batteries. However, graphite materials have no satisfactory energy density owing to the limited capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, using the DFT-PBE method, computations revealed that As 2 S 3 can reduce the NaPS shuttling and improve the cathode conductivity, leading to enhanced cycling and Coulombic efficiency . The ferroelectric In 2 Se 3 cathode was also computationally proposed to effectively decrease the kinetic barrier of the Na 2 S decomposition reaction …”
Section: Introductionmentioning
confidence: 99%
“…26 The ferroelectric In 2 Se 3 cathode was also computationally proposed to effectively decrease the kinetic barrier of the Na 2 S decomposition reaction. 27 Apart from cathode engineering, various strategies for strengthening the sodium anode are introduced to prevent the decomposition of NaPS, where long-chain NaPS are highly soluble in carbonate-based electrolytes and can diffuse through the electrolyte to deposit on the sodium-metal anode surface and undergo redox reactions to form short-chain NaPS films. 19 The cyclability and wettability can be enhanced by the alloying of Na anode.…”
Section: Introductionmentioning
confidence: 99%